2014
DOI: 10.1074/jbc.m114.550004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Endogenous N-Arachidonoylserotonin by Human Cytochrome P450 2U1

Abstract: Background: Cytochrome P450 (P450, CYP) 2U1 is an "orphan" enzyme, only reported to catalyze some fatty acid oxidations. Results: Metabolomic screening led to the identification of N-arachidonoylserotonin as a substrate. Conclusion: P450 2U1 catalyzes oxygenation at C-2 of the indole ring. Significance: The localization of P450 2U1 and its metabolism of an inhibitor of fatty acid amide hydrolase may indicate a function in brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…AA-5-HT is a selective fatty acid amide hydrolase (FAAH) inhibitor that was consistently increased in the E+ plasma. AA-5-HT-induced FAAH inhibition increases four-fold when oxidized by CYP450's (Siller et al, 2014). AA-5-HT is present in the GI tract of multiple species (Verhoeckx et al, 2011) and it was recently detected in bovine and human brain and thymus tissues, indicating that it becomes systemic (Siller et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…AA-5-HT is a selective fatty acid amide hydrolase (FAAH) inhibitor that was consistently increased in the E+ plasma. AA-5-HT-induced FAAH inhibition increases four-fold when oxidized by CYP450's (Siller et al, 2014). AA-5-HT is present in the GI tract of multiple species (Verhoeckx et al, 2011) and it was recently detected in bovine and human brain and thymus tissues, indicating that it becomes systemic (Siller et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…AA-5-HT-induced FAAH inhibition increases four-fold when oxidized by CYP450's (Siller et al, 2014). AA-5-HT is present in the GI tract of multiple species (Verhoeckx et al, 2011) and it was recently detected in bovine and human brain and thymus tissues, indicating that it becomes systemic (Siller et al, 2014). AA-5-HT is sensitive to dietary fat (Verhoeckx et al, 2011) and decreased uptake of VFA (Dijkstra et al, 1993;Foote et al, 2013;Foote et al, 2014), along with significant increases in putative plasma glycerophospholipid metabolites seen herein, may play a role in decreased nutrient utilization, resulting in lowered weight gains which is a finding consistently reported in chronic E+ grazing (Oliver, 1997;Strickland et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this case, samples were extracted with ethyl acetate and cyclohexane, in the presence of deuterated internal standards, and analyzed by a triple quadrupole LC/MS/MS [50]. In fact, very recently, the identification of an oxidative product of AA-5-HT by cytochrome P450 in human brain tumor tissues was reported [52], using an UPLC coupled to an LTQ for isotope dilution experiments, Q-TOF to determine the accurate mass and, finally, a 1 H-NMR analysis to confirm the chemical structure. Regarding N-acylserotonins, very little is known about these mediators because only a few papers reported their endogenous formation.…”
Section: Analytical Approaches Available For Small Molecules Of the Ementioning
confidence: 99%
“…The authors also observed that NAS formation in vitro was stimulated by the addition of serotonin to intestinal tissue incubations and that, in living mice, the pattern of their formation is dependent on the relative amount of fatty acids in the diet. Although further experiments aiming at understanding the biosynthetic mechanism of NAS have not yet been performed, a very recent study, apart from demonstrating its presence in bovine and human brain, showed that AA-5-HT can be efficiently oxidized on the 2-position of the indole ring to the corresponding keto-derivative by cytochrome P450 2U1 [73]. The authors also confirmed FAAH inhibitory activity in vitro for most of the NASs and showed that they are able to stimulate GLP-1 secretion from the ileum [8].…”
Section: Synthesis As Faah Inhibitors and Recent Discovery As Endogenmentioning
confidence: 99%
“…For example, the levels of N-docosahexaenoylserotonin and N-eicosapentaenoyl-serotonin, which, unlike other saturated and monounsaturated NASs, were previously shown to be almost as potent as AA-5-HT at inhibiting FAAH and antagonizing TRPV1 [64], were higher in mice fed with a diet containing fish oil, which is an abundant source of docosahexaenoic and eicosapentaenoic acids. The ensuing metabolite, 2-oxo-AA-5-HT, was fourfold less active than AA-5-HT at inhibiting FAAH, but was not tested on TRPV1 [73]. Although further experiments aiming at understanding the biosynthetic mechanism of NAS have not yet been performed, a very recent study, apart from demonstrating its presence in bovine and human brain, showed that AA-5-HT can be efficiently oxidized on the 2-position of the indole ring to the corresponding keto-derivative by cytochrome P450 2U1 [73].…”
Section: Synthesis As Faah Inhibitors and Recent Discovery As Endogenmentioning
confidence: 99%